Design Of CMOS Power Amplifier For Ultra-Wideband (UWB) Transmitter - Mohd Hassan, Siti Maisurah (2008)
This thesis presents the design and implementationof three PAs for 3.1 to 4.8GHz UWB communication system in 0.18 um RF CMOS technology. The design methodology presented here covers the steps from circuit implementation up to validation of the measurement results of the fabricated chip. Circuit analysis that covers on wide bandwidth amplifier is discussed followed by computer simulations that include optimization process of the PAs. Layout design of the PAs including design considerations for individual components are described followed by the post layout simulation that include parasitic extraction from the layouts.